Voidability of transaction as absolute legal consequence of noncompliance with its notarial form - I.I. Bagautdinov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper analyzes the provisions of the Civil Code of the Russian Federation concerning the elements of transaction form. In particular, the essence of these elements has been investigated. Differences of the consequences of incompliance with them have been analyzed. It has been established that the notarial form of transaction consists of general (document, party signature, and seal impression) and special (notary certification statement) elements. Incompliance with the special element of the notarial form only results in its voidability. In its turn, incompliance with other (general) elements of the notarial form characterizes it as void. It has been emphasized that the transaction can be considered void only upon conclusion and can not be void in case it is not concluded. Using these rules, as considered by the author, favors uniformity in interpretation and application of legal regulations in courts.